2012
DOI: 10.1021/jo300569c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Substituent Effects on Proline Catalysis of Aldol Reactions in Water

Abstract: Derivatives of 4-hydroxyproline with a series of hydrophobic groups in well-defined orientations have been tested as catalysts for the aldol reactions. All of the modified proline catalysts carry out the intermolecular aldol reaction in water and provide high diastereoselectivity and enantioselectivity. Modified prolines with aromatic groups syn to the carboxylic acid are better catalysts than those with small hydrophobic groups (1a is 43.5 times faster than 1f). Quantum mechanical calculations provide transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…Among the various catalysts for direct asymmetric aldol reaction, a series of organocatalysts derived from L‐proline are of particular significance. This is why many efforts have been made to modify the structure of L‐proline so as to improve selectivity and reusability, reduce load, and avoid the use of organic solvent . To overcome these drawbacks, researchers also have made attempts to graft organocatalysts with suitable supports .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various catalysts for direct asymmetric aldol reaction, a series of organocatalysts derived from L‐proline are of particular significance. This is why many efforts have been made to modify the structure of L‐proline so as to improve selectivity and reusability, reduce load, and avoid the use of organic solvent . To overcome these drawbacks, researchers also have made attempts to graft organocatalysts with suitable supports .…”
Section: Introductionmentioning
confidence: 99%
“…This is why many efforts have been made to modify the structure of L-proline so as to improve selectivity and reusability, reduce load, and avoid the use of organic solvent. [9][10][11][12][13][14] To overcome these drawbacks, researchers also have made attempts to graft organocatalysts with suitable supports. [15][16][17][18] The resultant immobilized organocatalysts offer some advantages over small organic catalysts, such as recyclability, simple reaction set-up plus easy experimental procedure, and nontoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Following ad ifferent approach, Schafmeister and co-workers, [49] synthesized af amilyo fs pirocyclic imidazolidinones as organocatalystsf or the asymmetric aldol reactiono fc yclic ketones and aldehydes in water.O ft he tested derivatives, catalyst 83 exhibited the best results and gave products anti-37 and 63 in good yields and excellent diastereo-and enantioselectivity with 1mol %o fc atalyst (Scheme 19A). DFT calculations in water showed that the Houk-List transition structure, which leads to the formation of the major isomers, has as tabilizing edge-to-face hydrophobic interaction between the aromatic ring of the aldehyde and the benzyl group of the organocatalyst (Scheme 19B).…”
Section: Amide Derivativesmentioning
confidence: 99%
“…63 and 37 promoted by organocatalyst 83.B)Houk-List transition structure (M06-2X(SMD, solvent = H 2 O)/6-31G* level of theory) associated with the formation of the majori somer formed in the reaction between cyclohexanone and benzaldehydei nthe presence of 83.The edge-to-face hydrophobic contact between the phenyl groupo f benzaldehyde and the benzyl group of 83 is highlighted. Bond lengths are given in .C artesian coordinates taken from Ref [49]…”
mentioning
confidence: 99%
“…Carboxylic acid moiety of L-proline, hydroxyl group of 4-hydroxy-L-proline individually or both groups simultaneously were reported to be modified in order to enhance the hydrophobicity of L-proline. Of late, Zhao et al [33] have reported their investigation on the hydrophobic substituent effects on proline catalyzed aldol reactions in water. They have synthesized a series of modified praline 2 that exhibit excellent diastereoselectivity and enantioselectivity with very low catalytic loading in an aldol reaction in water, which is also supported by DFT TS model of the corresponding aldolization reaction.…”
Section: Introductionmentioning
confidence: 99%